Characterization of vascular niche in systemic sclerosis by spatial proteomics - Rigau, Aleix Rius; Li, Yi-Nan; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Bruch, Peter-Martin; Koziel, Sarah; Devakumar, Veda; Gabrielli, Armando; Kreuter, Alexander; Wang, Jiucun; Dietrich, Sascha; Schett, Georg; et al. (Circulation research, 2024)
BACKGROUND: - Systemic sclerosis (SSc) is a connective tissue disease that can serve as a model to study vascular changes in response to inflammation, autoimmunity, and fibrotic remodeling. Although microvascular changes are the earliest histopathologic manifestation of SSc, the vascular pathophysiology remains poorly understood. - METHODS: - We applied spatial proteomic approaches to deconvolute the heterogeneity of vascular cells at the single-cell level in situ and characterize cellular alterations of the vascular niches of patients with SSc. Skin biopsies of patients with SSc and control individuals were analyzed by imaging mass cytometry, yielding a total of 90 755 cells including 2987 endothelial cells and 4096 immune cells. - RESULTS: - We identified 7 different subpopulations of blood vascular endothelial cells (VECs), 2 subpopulations of lymphatic endothelial cells, and 3 subpopulations of pericytes. A novel population of CD34+;αSMA+ (α-smooth muscle actin);CD31+ VECs was more common in SSc, whereas endothelial precursor cells were decreased. Co-detection by indexing and tyramide signal amplification confirmed these findings. The microenvironment of CD34+;αSMA+;CD31+ VECs was enriched for immune cells and myofibroblasts, and CD34+;αSMA+;CD31+ VECs expressed markers of endothelial-to-mesenchymal transition. The density of CD34+;αSMA+;CD31+ VECs was associated with clinical progression of fibrosis in SSc. - CONCLUSIONS: - Using spatial proteomics, we unraveled the heterogeneity of vascular cells in control individuals and patients with SSc. We identified CD34+;αSMA+;CD31+ VECs as a novel endothelial cell population that is increased in patients with SSc, expresses markers for endothelial-to-mesenchymal transition, and is located in close proximity to immune cells and myofibroblasts. CD34+;αSMA+;CD31+ VEC counts were associated with clinical outcomes of progressive fibrotic remodeling, thus providing a novel cellular correlate for the crosstalk of vasculopathy and fibrosis.